Evaluasi Sensitivitas Colletotrichum sp. Penyebab Penyakit Antraknosa pada Cabai di Lampung terhadap beberapa Fungisida - Maryono, Tri; Nurzi, Rosma; Ginting, Cipta; Dirmawati, Suskandini Ratih (Fakultas Pertanian Universitas Padjadjaran, 2025)
Anthracnose is a major disease of chili peppers caused by complex of Colletotrichum species. Intensive application of fungicides is the main choice for control anthracnose. This study aimed to evaluate the sensitivity of Colletotrichum spp. to fungicides and determine the effective concentration to control Colletotrichum spp. This study was conducted from March to July 2024 at the Plant Disease Laboratory, Faculty of Agriculture, Lampung University. Anthracnose pathogens were isolated from Tegineneng District, Pesawaran Regency, Lampung Province. Sensitivity tests were conducted using the recommended concentration with poisoned food techniques. The effective concentration determination test was carried out only on fungicides that showed a resistance response using the poisoned food technique. The fungicides tested were those used by farmers in the location where the samples were taken. The sensitivity test results showed that the fungus Colletotrichum spp. from Tegineneng District was highly resistant to propineb. Colletotrichum spp. from locations 3 and 4 are still sensitive to carbendazim, but from locations 1 and 2 are resistant. Colletotrichum spp. from locations 2, 3, and 4 were still very sensitive to mankozeb, while those from location 1 were moderately resistant. The effective concentration of propineb for locations 1, 3, and 4 was 5x the recommended concentration, and for location 2 was 4x the recommended concentration. The effective concentration of carbendazim for location 1 was 5x the recommended concentration, and for location 2 was 2x the recommended concentration. The effective concentration of mancozeb fungicide at location 1 was 2x the recommended concentration.